Effects of Meconopsis aculeata Royle Extracts on Leukocytosis and Eosinophilia Induced by Milk in Albino Mice: Anti-asthmatic Property (Journal of Scientific Research, 2023)
Meconopsis aculeata Royle is a herb with medicinal value, traditionally used by the local people of the Himalayan range for its anti-asthmatic potential. The present work aims to determine the effects of the methanolic whole plant extract of M. aculeata for the management of allergy (asthma) in mice as less work has been done on this potential of the plant. We also determined the in vitro antioxidant and anti-inflammatory potential and identification of the plant’s active phytoconstituents through GC-MS. It was found that M. aculeata extracts inhibited (89.68 %) free radicals in a better way when compared with standard ascorbic acid (73.47 %) at a higher concentration of 250 μg/mL. Plant extract inhibited (85.52 %) denaturation of protein when compared with standard aspirin (76.47 %) at a higher concentration of 250 μg/mL. Methanolic extracts (at 100-200 mg/kg, intraperitoneally) significantly decreased elevated leukocyte and eosinophil count in mice that were induced by milk. The anti-asthmatic potential of this plant may be due to identified phytoconstituents like Stigmast-5-en-3-ol; Protopine; 9,12-Octadecadienoic acid; and 9,12-Octadecadienoic acid (Z, Z), methyl ester as these possesses anti-asthmatic and antihistaminic properties. Thus, M. aculeata can be used to treat allergies like asthma, and inflammation and reduce oxidative stress.